Zoogeographic significance of Dmanisi large mammal assemblage. Issue 163 (February 2022) - Bartolini-Lucenti, Saverio; Cirilli, Omar; Pandolfi, Luca; Bernor, Raymond Louis; Bukhsianidze, Maia; Carotenuto, Francesco; Lordkipanidze, David; Tsikaridze, Nikoloz; Rook, Lorenzo
Abstract: We undertake a comparative mammalian zoogeographic analysis with the aim of revealing the extent to which the Dmanisi Early Pleistocene large mammal assemblage resembles, at the genus level, African, Arabian, and Eurasian localities of similar age. The inclusion of Old World Pliocene and Pleistocene mammalian faunas provides us with insights into the provincial origins of specific mammalian taxa and permits us to assess the relative affiliation of the Dmanisi mammalian faunas to other faunas in the Old World. Our analysis also allows us to consider hypotheses about the timing and direction of zoogeographic connections between western Eurasia and Africa during the Early Pleistocene. We utilize multiple zoogeographic analytical tools as a cross-comparison of Dmanisi with 42 other Eurasian and African mammalian-bearing localities between 2.7 and 0.7 Ma. Overall, we find that Dmanisi compares most closely with a subgroup of Greek, Italian, and Spanish localities that are slightly younger than Dmanisi itself. This could suggest a progressive dispersal from East to West of the large mammal communities during the late Early Pleistocene and the first occurrence at Dmanisi, and then later in Western Europe, of some taxa such as Stephanorhinus ex gr. etruscus-hundsheimensis, Equus altidens, Bison georgicus, Soergelia minor, Megantereon whitei, Canis borjgali, Canis ( Xenocyon ) lycaonoides . Dmanisi's habitats included drier areas, probably of open wooded savannah and grassland and by mountainous to semiarid rocky terrain. There is evidence that Dmanisi records short intervals of increased aridity in the middle part of the succession contemporaneous with the occurrence of Homo.